Factors that influence the customer behaviour dining-out in restaurant during and post COVID-19 / Munirah Hamid … [et al.] - Hamid, Munirah; Abdul Jalil, Norfarisya Izleen; Rosaidi, Rabiatul Atirah; Abd Ghani, Fatimah; Wan Abd Rahman, Wan Zuhaila (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
The global COVID-19 pandemic has caused a significant change in people's food behaviours and preferences. The purpose of this research is to identify the factors that affecting the restaurant customer behaviour and to investigate the most significant factors influencing the customer behaviour when dining out during and post COVID-19. The customers’ choice usually depending on several factors and criteria such as food quality, service quality and the restaurant environment. This quantitative research has been conducted specifically focusing only in Dungun, Terengganu. by distributing the online questionnaire to the customers who have experienced dining out at restaurants both during and post-COVID-19. As a result, 130 respondents took part in the survey and answered all the questions in four (4) sections in the questionnaire given.